2021
DOI: 10.1115/1.4050818
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Loading-Induced Interstitial Fluid Dynamics in Osteon of Osteogenesis Imperfecta Bone

Abstract: Osteogenesis Imperfecta (OI), also known as 'brittle bone disease', is a genetic bone disorder. OI bones experience frequent fractures. It is observed physical activity is equally beneficial in reducing OI bone fractures in both children and adults as mechanical stimulation improves bone mass and strength. Loading-induced mechanical strain and interstitial fluid flow stimulates bone remodeling activities. Several studies have characterized strain environment in OI bones, whereas, a very few studies attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…A maximum radial pore pressure of 532 Pa is observed in healthy osteon, whereas, OI osteon experiences a pore-pressure of 137 Pa. Shrivas et al 43 , Wu and Chen 36 and Chen et al 54 also reported a similar decline in pore-pressure when one of the osteon walls were considered impermeable. This validates the analytical computation of pore-pressure done in the present work.…”
Section: Spatio-temporal Pore-pressure Distributionmentioning
confidence: 90%
See 2 more Smart Citations
“…A maximum radial pore pressure of 532 Pa is observed in healthy osteon, whereas, OI osteon experiences a pore-pressure of 137 Pa. Shrivas et al 43 , Wu and Chen 36 and Chen et al 54 also reported a similar decline in pore-pressure when one of the osteon walls were considered impermeable. This validates the analytical computation of pore-pressure done in the present work.…”
Section: Spatio-temporal Pore-pressure Distributionmentioning
confidence: 90%
“…Pore-pressure significantly reduces in OI osteon as compared to healthy osteon. 15.41 43 13.49 43 M t (GPa) 38.80 43 12.07 43 K l (GPa) 13.53 43 10.15 43 M l (GPa) 37.18 43 7.25 Case II (displacement constraint boundary) also experiences a nonlinear increase in pore pressure from inner osteon wall to outer osteon wall. Nevertheless, the pore-pressure enhance in Case II for both healthy and OI osteons (Figure 3(c) and (d)).Wu and Chen 36 had noticed a similar trend of pore-pressure distribution in a hollow osteon subjected to cyclic sinusoidal loading.…”
Section: Spatio-temporal Pore-pressure Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid was set as blood with a density and viscosity of 1060 kg m −3 and 0.003 kg m −1 s − 1 . [ 25 ] The fluid velocity was 80 μm s −1 at the scaffold inlet, [ 26 ] the walls were set as no‐slip boundaries, and the outlet pressure was set as 0 Pa (Figure 1d). Fluid flow through the cell generated the FSS.…”
Section: Methodsmentioning
confidence: 99%
“…Many factors affect the ability of bone tissue to regenerate and repair itself. 6 Severe bone defects can be caused by tumor resection, 7,8 severe trauma, 9 infection, 10 congenital malformation, osteogenesis imperfecta, 11 rheumatoid arthritis, 12 and osteoporosis. 13,14 Bone tissue healing involves a complex signaling cascade, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%